2006
DOI: 10.1111/j.1574-695x.2006.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited contribution of Toll-like receptor 2 and 4 to the host response to a fungal infectious pathogen,Cryptococcus neoformans

Abstract: The present study was designed to elucidate the role of Toll-like receptor (TLR) 2 and TLR4 in the host response to Cryptococcus neoformans. Both TLR2 knockout (KO) and TLR4KO mice produced interleukin-1beta (IL-1beta), IL-6, IL-12p40 and tumor necrosis factor-alpha (TNF-alpha) in sera and cleared this fungal pathogen from infected lungs at a comparable level to control littermate (LM) mice. Synthesis of these cytokines was not significantly different in the lungs of these KO mice and LM mice, although IL-1bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 23 publications
4
76
2
6
Order By: Relevance
“…In contrast, in our study (14), TLR2 and TLR4 did not seem to be involved in the host-protective response to this infection. In contrast, TLR4 was reported to sense glucuronoxylomannan, a major component of the polysaccharide capsule of Cn, in Chinese hamster ovary cells (15).…”
Section: Ryptococcus Neoformans (Cn)contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, in our study (14), TLR2 and TLR4 did not seem to be involved in the host-protective response to this infection. In contrast, TLR4 was reported to sense glucuronoxylomannan, a major component of the polysaccharide capsule of Cn, in Chinese hamster ovary cells (15).…”
Section: Ryptococcus Neoformans (Cn)contrasting
confidence: 99%
“…These findings suggested the possible involvement of certain TLRs. However, involvement of TLR2 and TLR4 in the host defense responses against this infection remains to be substantiated (12)(13)(14). Recent studies have identified the involvement of TLRs in the recognition of nucleic acids; including TLR3 for dsRNA, TLR7/8 for ssRNA, and TLR9 for unmethylated CpG motif-containing DNA (18, 38 -40).…”
Section: Discussionmentioning
confidence: 99%
“…While TLR2 and TLR4 have been shown to respond to C. neoformans products, 42,43 their in vivo effects are minimal or highly inconsistent between different studies. 44,45 TLR9 is a member of the TLR family located intracellularly in the cytoplasm and binding to cytoplasmic endosomes of dendritic cells (DC), macrophages, and other cells of the immune system. 46 TLR9 coupling/signaling occurs presumably after the microbe becomes ingested and lysed within the endosome, exposing the CpG DNA (TLR9 ligand).…”
mentioning
confidence: 99%
“…C. neoformans activates dendritic cells via TLR9 [19] and DC-SIGN [20]. In contrast to other fungi, it does not induce signaling through Dectin-1 [21] or TLR4 [22] and only mildly affects cytokine expression via TLR2 [22]. P. jirovecii, on the other hand, requires Dectin-1 [7] and TLR2, [23] and MR, to induce cytokine release by phagocytes.…”
Section: Recognition Of Fungimentioning
confidence: 97%